Chick Hippocampal Formation Displays Subdivision- and Layer-Selective Expression Patterns of Serotonin Receptor Subfamily Genes - Fujita, Toshiyuki; Aoki, Naoya; Mori, Chihiro; Fujita, Eiko; Matsushima, Toshiya; Homma, Koichi J.; Yamaguchi, Shinji (Frontiers in Physiology, 2022)
Hippocampal formation (HF) plays a key role in cognitive and emotional processing in mammals. In HF neural circuits, serotonin receptors (5-HTRs) modulate functions related to cognition and emotion. To understand the phylogenetic continuity of the neural basis for cognition and emotion, it is important to identify the neural circuits that regulate cognitive and emotional processing in animals. In birds, HF has been shown to be related to cognitive functions and emotion-related behaviors. However, details regarding the distribution of 5-HTRs in the avian brain are very sparse, and 5-HTRs, which are potentially involved in cognitive functions and emotion-related behaviors, are poorly understood. Previously, we showed that 5-HTR1B and 5-HTR3A were expressed in chick HF. To identify additional 5-HTRs that are potentially involved in cognitive and emotional functions in avian HF, we selected the chick orthologs of 5-HTR1D, 5-HTR1E, 5-HTR1F, 5-HTR2B, 5-HTR5A, and 5-HTR7 and performed in situ hybridization in the chick telencephalon. We found that 5-HTR1D, 5-HTR1E, 5-HTR5A, and 5-HTR7 were expressed in the chick HF, especially 5-HTR1D and 5-HTR1E, which showed subdivision- and layer-selective expression patterns, suggesting that the characteristic 5-HT regulation is involved in cognitive functions and emotion-related behaviors in these HF regions. These findings can facilitate the understanding of serotonin regulation in avian HF and the correspondence between the HF subdivisions of birds and mammals.